Analisis Strategi Pemasaran Penjualan Tanah Kavling Moani Property Desa Limbung Kabupaten Kubu Raya - Aswandi, Aswandi; Firayanti, Yuni; Rosadi, Rosadi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the marketing strategy applied by Moani Property in the sale of land plots in Limbung Village, Kubu Raya Regency. With a qualitative approach, this study explores the key factors that affect the effectiveness of marketing strategies, including price, strategic location, digital promotion, purchase incentives, and customer satisfaction. The data was collected through in-depth interviews with Moani Property management, the marketing team, as well as consumers who had purchased land plots, then analyzed using thematic analysis methods. The results of the study show that incentive-based marketing strategies, such as giving free fruit seeds, marketing through social media, and flexible payment systems without interest, are the main factors that attract buyers. In addition, strategic location, clear land legality, and word-of-mouth promotion also play an important role in the purchase decision. This finding provides insight for Moani Property in developing more innovative marketing strategies and increasing competitiveness in the property industry.